REVERSE ENGINEERING SACRACY: AN ETHNOGRAPHY OF REPOSITIONING THE TOTALITY OF TRADITIONAL ARTS AT THE INTERSECTION OF VIRTUAL INFRASTRUCTURE AND DIGITAL COMMUNAL RESISTANCE - Suryanti Suryanti; Hartitom Hartitom (PT. Antis International Publisher, 2026)
Objective: This study examines the challenges arising from the encounter between the sacred totality of traditional art and the logic of virtual infrastructure, which drives the process of sacrality reengineering. This process involves the deconstruction of the inseparable unity of ritual, art, community, and cosmology, detaching them from their sacred contexts and reassembling them within digital platform formats. Method:Employing a literature review methodology, the study analyzes ethnographic books, national and international scholarly journal articles, and relevant research reports. Results: The findings reveal four principal insights. First, the morphology of sacredness in traditional art within the pre-digital context is constituted by elements of sacred space, sacred time, heirloom objects, and the roles of ritual performers, forming an indivisible totality. Second, the mechanism of sacrality reengineering unfolds in three stages: the disintegration of aesthetic elements from the ritual core, reformatting in accordance with platform algorithmic logic, and the repositioning of meaning into entertainment content, virtual identity, and digital tourism commodities. Third, a crossroads emerges where customary authority intersects with digital metrics, prompting negotiations of identity for traditional artists transitioning into content creators and causing cultural legitimacy dissonance. Novelty: Fourth, indigenous communities develop a spectrum of digital communal resistance, ranging from passive resistance through access restrictions and platform neglect to active-adaptive resistance via sacred digital archives, counter-narratives, and the creation of exclusive communally based digital spaces. The study’s implications underscore the necessity of formulating cultural heritage protection policies grounded in the digital sovereignty of indigenous communities.